The diagnostic performance parameters of Narrow Band Imaging: A preclinical and clinical study. (September 2016) - Ottaviani, Giulia; Gobbo, Margherita; Rupel, Katia; D'Ambros, Marta; Perinetti, Giuseppe; Di Lenarda, Roberto; Martinelli, Valentina; Bussani, Rossana; Tirelli, Giancarlo; Lodi, Giovanni; Zacchigna, Serena; Biasotto, Matteo
Highlights: Narrow Band Imaging fosters premalignant and malignant oral lesions early diagnosis. Narrow Band Imaging stands as an efficient diagnostic method. Narrow Band Imaging reliability is elevated both in preclinical and clinical study. Abstract: Objectives: The oral carcinoma is a widespread pathology and still presents poor prognosis. Among the available procedures for its early detection, Narrow Band Imaging technique allows to assess potential vascular network abnormalities. The reliability of this technique in the detection of dysplastic and neoplastic oral lesions was evaluated in a preclinical and clinical study. Materials and methods: In the preclinical study, a chemical oral carcinogen was administered to 50 mice to induct both dysplastic and neoplastic oral lesions. In the clinical study 91 patients, bearing suspicious premalignant and malignant oral lesions, have been included. Images of animals' and patients' lesions were acquired under white and Narrow Band Imaging light prior to biopsy. Two expert raters examined the images and classified lesions, which were eventually compared to the histological diagnosis. The diagnostic performance included sensitivity, specificity, positive likelihood ratio, positive and negative predictive values, accuracy, percentages and degree of agreement between raters' evaluation and the histological report. Results: In the preclinical study sensitivity ranged from 0.57 to 1, specificity from 0.85 to 0.99, positive likelihood ratio from 6.54 to 65.04, positive predictive values from 0.32 to 0.96, negative predictive values from 0.91 to 1 and accuracy from 0.86 to 0.98. In the clinical study sensitivity ranged from 0.63 to 0.99, specificity from 0.89 to 1, positive likelihood ratio from 8.45 to 61.47, positive predictive values from 0.59 to 0.96, negative predictive values from 0.78 to 1 and accuracy from 0.82 to 0.99. Conclusion: Narrow Band Imaging is an accurate technique, which holds a great potential for tumour angiogenesis evaluation and for the subsequent early detection of suspicious premalignant and malignant oral lesions.